دراسة تجريبية لآلة تبريد امتصاصية شمسية صغيرة الاستطاعة - جابر ديبة (Tishreen University, 2019)
تم في هذا البحث القيام بدراسة تجريبية لآلة تبريد امتصاصية مخبرية ذات استطاعة اسمية 10 [kW] تعمل بوساطة منابع حرارية مختلفة وباستخدام محاليل ثنائية مختلفة وهي مزودة بحساسات كافية لقياس درجات الحرارة والتدفقات والضغوط في مواقع متعددة. تم تحديد خواص تشغيل الآلة لأغراض التكييف باستخدام المحلول الثنائي (الماء وبروميد الليثيوم) عند شروط حدية مختلفة, وتحليل تلك الخواص ومناقشتها. أثبتت نتائج التجارب إمكانية عمل آلة التبريد الامتصاصية الشمسية بشكل مستمر عند درجة حرارة تسخين للمولد حوالي 60 [°C] منتجة الماء البارد في المبخر بدرجة حرارة أقل من 10 [°C] وبعامل أداء (عامل إحداث برودة) تتراوح قيمته وسطياً 0,5 وهذا ما يمكننا من استخدام المجمعات الشمسية المسطحة لتشغيل تلك الآلة حيث تتميز تلك المجمعات ببساطة صنعها ورخص ثمنها. In this research, an absorption cooling system of nominal capacity 10 [kW] has been built and tested; it works by different sources of heat and by different working fluids, it is equipped with adequate sensors for measuring temperature, flows and pressures in multiple locations. The features of operating the machine for air conditioning has been determined, analyzed and discussed with the working fluid "water-Lithium Bromide" by different boundary conditions. The results of experiments proved the possibility of the work of solar absorption cooling machine continuously at the heating temperature of the generator of 60 [°C] producing cold water in the evaporator at a temperature less than       10 [°C] with a coefficient of performance 0,5 and this enables us to use Simple and cheap flat solar collectors for the operation of the machine.